Kearifan Lokal Urang Lom Sebagai Modal Sosial Dalam Pelestarian Hutan Benak Di Tengah Ekspansi PT.GPL Di Dusun Pejem, Kabupaten Bangka - A Zulkarnain, Ariandi; Darmawan, Budi (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2024)
For industrial purposes, forests originally used for agriculture have been converted into palm coconut plantations and extractive land. The Benak Forest, on the other hand, is the only forest still available to the Mapur tribe. They believe that their lives will end if Benak's native forests disappear. Mapur has a unique way of managing forests and land. They believe that forests should be managed on the basis of natural sustainability, local stability, and economic needs. The focus of this research is to find out the benefits of local wisdom as a social capital in keeping the Benak Forest as PT. GPL continues to grow. Therefore, this research is essential to provide information to governments and stakeholders about the importance of saving and preserving the Benak Forest for the people of the Mapur's Wan Lom Tribe to maintain the balance of ecosystems and living resources. This research uses a qualitative approach with an interpretative paradigm. The results of the research show that capitalism, in which social relations are determined by the relations of production, causes tribal societies, or peoples, to be isolated in their own land. Because they have no control over their ownership and rights to their land, discrimination and stereotypes, land rights, and loss of culture are the result of alienation that is dangerous for the survival of communities and forests.